Aryl Hydrocarbon Receptor Ablation in Cardiomyocytes Protects Male Mice From Heart Dysfunction Induced by NKX2.5 Haploinsufficiency. (14th August 2017) - Wang, Qin; Fan, Yunxia; Kurita, Hisaka; Jiang, Min; Koch, Sheryl; Rao, Marepalli B.; Rubinstein, Jack; Puga, Alvaro
Abstract: Epidemiological studies in humans and research in vertebrates indicates that developmental exposure to 2, 3, 7, 8-tetrachlorodibenzo- p -dioxin (TCDD), a ubiquitous and biopersistent environmental toxicant, is associated with incidence of early congenital heart disease in the embryo and later in the adult. TCDD-mediated toxicity depends on the aryl hydrocarbon receptor (AHR) but the role of the TCDD-activated AHR in cardiac function is not well-defined. To characterize the mechanisms responsible for AHR - mediated disruption of heart function, we generated several mouse strains with cardiomyocyte-specific Ahr gene knockout. Here, we report results on one of these strains in which the Ahr gene was deleted by cre recombinase regulated by the promoter of the cardiomyocyte-specific Nkx2.5 gene. We crossed mice with lox P-targeted Ahr fx/fx alleles with Nkx2.5 +/cre mice bearing a "knock-in" cre recombinase gene integrated into one of the Nkx2.5 alleles. In these mice, loss of one Nkx2.5 allele is associated with disrupted cardiac development. In males, Nkx2.5 hemizygosity resulted in cardiac haploinsufficiency characterized by hypertrophy, dilated cardiomyopathy, and impaired ejection fraction. Ahr ablation protected Nkx2.5 +/cre haploinsufficient males from cardiac dysfunction while inducing a significant increase in body weight. These effects were absent or largely blunted in females. Starting at 3 months of age, mice were exposed by oral gavage to 1 μg/kg/week of TCDD or control vehicle for an additional 2 months. TCDD exposure restored cardiac physiology in aging males, appearing to compensate for the heart dysfunction caused by Nkx2.5 hemizygosity. Our findings underscore the conclusion that deletion of the Ahr gene in cardiomyocytes protects males from heart dysfunction due to NKX2.5 haploinsufficiency.